Inhibition of NF-kappaB enhances the cytotoxicity of virus-directed enzyme prodrug therapy and oncolytic adenovirus cancer gene therapy. - Palmer, D; Chen, M; Searle, P; Kerr, D; Young, L (2005)
Virus-directed enzyme prodrug therapy utilizing the bacterial enzyme nitroreductase delivered by a replication-defective adenovirus vector to activate the prodrug CB1954 is a promising strategy currently undergoing clinical trials in patients with a range of cancers. Similarly, selectively replicating oncolytic adenoviruses are entering clinical trials. An understanding of interactions between vector and target cell are critical to the development of these strategies. We demonstrate that adenovirus vectors activate cellular pathways that promote cell survival in an NF-kappaB-dependent manner, and consequently have a negative effect on the efficacy of cell killing induced by cancer gene therapy strategies. This provides a potential therapeutic target to enhance the cytotoxicity of these approaches.